2020
DOI: 10.1074/jbc.ra120.013792
|View full text |Cite
|
Sign up to set email alerts
|

A terminal α3-galactose modification regulates an E3 ubiquitin ligase subunit in Toxoplasma gondii

Abstract: Skp1, a subunit of E3 Skp1/Cullin-1/F-box protein ubiquitin ligases, is modified by a prolyl hydroxylase that mediates O2 regulation of the social amoeba Dictyostelium and the parasite Toxoplasma gondii. The full effect of hydroxylation requires modification of the hydroxyproline by a pentasaccharide that, in Dictyostelium, influences Skp1 structure to favor assembly of Skp1/F-box protein subcomplexes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…1A) (32). As a positive control, UDP-Gal was hydrolyzed by a T. gondii galactosyltransferase (TgGat1), which adds a terminal galactose to the pentasaccharide attached to the T. gondii Skp1 E3 ubiquitin ligase subunit (33). Second, in the presence of GDP-Fuc, TgHis6SPY fucosylated itself (OFT activity in cis), as shown by Western blotting with AAL ( Fig.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…1A) (32). As a positive control, UDP-Gal was hydrolyzed by a T. gondii galactosyltransferase (TgGat1), which adds a terminal galactose to the pentasaccharide attached to the T. gondii Skp1 E3 ubiquitin ligase subunit (33). Second, in the presence of GDP-Fuc, TgHis6SPY fucosylated itself (OFT activity in cis), as shown by Western blotting with AAL ( Fig.…”
Section: Resultsmentioning
confidence: 88%
“…We have not yet determined the effect of TgSPY knockout on cat infections, but we have observed that AAL-labeled assemblies are absent in the periphery of meiotic nuclei of sporulating oocysts (22). Finally, addition of O-Fuc is the second cytosolic glycosylation system present in T. gondii, which also adds a pentasaccharide to a hydroxyproline residue on Skp1, an E3 ubiquitin ligase subunit (33).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…1 A ) ( 32 ). As a positive control, UDP-Gal was hydrolyzed by a T. gondii galactosyltransferase ( Tg Gat1), which adds a terminal galactose to the pentasaccharide attached to the T. gondii Skp1 E3 ubiquitin ligase subunit ( 33 ). Second, in the presence of GDP-Fuc, His 6 Tg SPY fucosylated itself (OFT activity in cis ), as shown by western blotting with AAL ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have not yet determined the effect of Tg SPY knockout on cat infections, but we have observed that AAL-labeled assemblies are absent in the periphery of meiotic nuclei of sporulating oocysts ( 22 ). Finally, addition of O -Fuc is the second cytosolic glycosylation system present in T. gondii , which also adds a pentasaccharide to a hydroxyproline residue on Skp1, an E3 ubiquitin ligase subunit ( 33 ).…”
Section: Discussionmentioning
confidence: 99%